RELATIVE CLAUSE OMISSION FOUND IN TENET MOVIE BY CHRISTOPHER NOLAN - Octavian, Hermanda; Handayani, Nurma Dhona (Asosiasi dosen IDEBAHASA KEPRI, 2024)
This descriptive qualitative research aimed to identify instances of relative clause omission in the movie Tenet by director Christopher Nolan. A theory from Hewings (2013) was applied to determine relative clauses in the data source. Observation and documentation were used as data collection methods, with the analysis conducted descriptively using words and sentences. Out of the 44 utterances that contain relative clauses, there were 20 data represented relative clause omission found in the movie's dialogues. They were categorized by subordinator: 7 utterances omitting